Analisis Spesifikasi Kerusakan Lambung Kapal yang Melakukan Perbaikan di PT Dok dan Perkapalan Kodja Bahari Galangan II - Miftaah Bagus Hartawan; Muhammad Irsad Syafiq; Faiz Ilham Mumtaz; Faqih Dimas Suryadi; Siti Sahara (Jurnal Ilmiah Wahana Pendidikan, 2023)
The development of shipping in the maritime world must be followed by an increase in the quality of transportation equipment. The ship is a means of transportation used in connecting land. Ship care and maintenance is very important. Because the operation of the ship requires conditions that are really good and suitable for sailing (Ariany, 2014). Damage that occurs to the ship, especially to the hull, can affect the performance of the ship which will result in leakage. The hull is the part of the ship that affects the buoyancy of the ship. The buoyancy has a function as a force that will support the load that comes from passengers and the contents of the ship's cargo. Hull construction is part of the overall ship construction frame system as a ship wall that functions to withstand the compressive force of seawater and load-bearing during launching or impact from surrounding objects. The purpose of this analysis is to identify damage to the hull of ships that make repairs at PT Dok and Shipping Kodja Bahari Galangan II. The method used is an interview with one of the employees of DKB Galangan II. KAPRO Division and conduct a document study by collecting various documents related to the hull repair process at DKB Galangan II. The type of research used is descriptive qualitative. The hull is a very important part of a ship. The hull is the main structure of the ship that forms the body of the ship and provides buoyancy and structural strength. The hull consists of parts such as side walls (side boards), lower hull (body), upper hull (deck), and retaining structures (decks, masts, and so on). In order to minimize hull damage, it requires careful monitoring of the condition of the hull and regular maintenance. Quick and proper handling of damage will help avoid more serious damage and ensure the safety of the ship and its crew